El arco urbano en la arquitectura Maya - Laura Gilabert Sansalvador; Andrea Peiró Vitoria; Rosana Martínez Vanaclocha (Restauro Archeologico, 2017)
Urban arches are one of the most emblematic Mayan architecture elements, for their singularity and monumentality and also for their strategic urban location. They appear on its own or as a part of an ensemble, sometimes being part of the composition of a building façade, but always used in special settings, either generating access points to an enclosure or place, transitions between different urban spaces or emphasizing symbolically the access to relevant architectural ensembles. This paper presents the results of a documentation work of the urban arches identified in the Maya Lowlands, based on an in situ data gathering and the analysis of their features from the building technology, formal, functional and symbolic points of view.